Bovine and equine peritubular and intertubular dentin - Stock, S.R. (2014)
Dentin contains 1–2 μm diameter tubules extending from the pulp cavity to near the junction with enamel. Peritubular dentin (PTD) borders the tubule lumens and is surrounded by intertubular dentin (ITD). Differences in PTD and ITD composition and microstructure remain poorly understood. Here, a (~200 nm)(2), 10.1 keV synchrotron x-ray beam maps x-ray fluorescence and x-ray diffraction simultaneously around tubules in 15–30 μm thick bovine and equine specimens. Increased Ca fluorescence surrounding tubule lumens confirms PTD is present, and the relative intensities in PTD and ITD correspond to carbonated apatite (cAp) volume fraction of ~0.8 in PTD vs. 0.65 assumed for ITD. In the PTD near the lumen edges, Zn intensity is strongly peaked, corresponding to Zn content of ~0.9 mg/g for assumed concentration of ~0.4 mg/g for ITD. In the equine specimen, the Zn K-edge position indicates Zn(2+) is present, similar to bovine dentin [2], and the above edge structure is consistent with spectra from macromolecules related to biomineralization. Transmission x-ray diffraction shows only cAp, and the 00.2 diffraction peak (Miller-Bravais indices) width is constant from ITD to the lumen edge. The 00.2 cAp average preferred orientation is axisymmetric (about the tubule axis) in both bovine and equine dentin, and the axisymmetric preferred orientation continues from ITD through the PTD to the tubule lumen. These data indicate that cAp structure does not vary from PTD to ITD.